Educação de Jovens e Adultos (EJA): uma leitura a partir da Base Nacional Comum Curricular (BNCC) e do Currículo Paulista - Santos, Bruna Castriani Ferreira dos (Universidade Federal de São Carlos, 2023)
Youth and Adult Education (EJA), a basic education modality, has historically faced invisibility in official education documents in Brazil. The objective of this paper is to analyze how this modality is addressed in recent official education documents: the National Common Curricular Base (BNCC) and the São Paulo Curriculum (CP). In addition, it aims to delve deeper into the discussion of the political context surrounding this modality from the 20th century to the present day. To this end, qualitative and documentary research was applied through the exploration of the aforementioned documents. Regarding the perspectives obtained in the National Common Curriculum Base, Youth and Adult Education is little explored in the introduction and does not have any further visibility throughout the document. Regarding the perspectives obtained in the São Paulo Curriculum (CP), Youth and Adult Education has a space in the document with visibility to show that it is a basic education modality and to explore its specificity. The document takes the opportunity to develop the following fact: the methodologies applied in regular education are not applicable to EJA due to the diversity of the subjects and their experiences. The results corroborate the invisibility of Youth and Adult Education (EJA) in the documents, leading to the understanding that this modality has suffered and still suffers from disrespect from government agencies. The investigation helps to reinforce that the documents analyzed serve thousands of people and that this could be an opportunity to, even if minimally, guide curricular paths for this audience.
Youth and Adult Education (EJA): a reading from the National Common Curricular Base (BNCC) and the Paulista Curriculum
Keywords: Educação de Jovens e Adultos; Base Nacional Comum Curricular; Currículo Paulista; Youth and Adult Education; National Common Curricular Base; São Paulo Curriculum; CIENCIAS HUMANAS::EDUCACAO::CURRICULO